2017
DOI: 10.21101/cejph.a4408
|View full text |Cite
|
Sign up to set email alerts
|

Mumps in the Eastern Bohemia Region of the Czech Republic - a Serological Survey 2008-2012

Abstract: The data from our study, with a low number of positive samples in the first years of the study and an increase in the last two years, could suggest the occurrence of outbreaks every 4-6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the present study, it was observed that following SGIV infection, a significant accumulation of inflammatory cells occurred in the intestinal tissue of grouper, along with the up-regulation of the expression of pro-inflammatory cytokines including IL-1β, IL-6, IL-8, TNF-α, and NF-κB, indicating that SGIV invasion caused an intestinal inflammatory response. Studies related to rotavirus, reovirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), astrovirus, and other viruses have extensively reported cases of intestinal inflammation caused by viral infection [42]. NF-κB is hypothesized to serve as a significant transcription factor implicated in inflammatory diseases of the intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was observed that following SGIV infection, a significant accumulation of inflammatory cells occurred in the intestinal tissue of grouper, along with the up-regulation of the expression of pro-inflammatory cytokines including IL-1β, IL-6, IL-8, TNF-α, and NF-κB, indicating that SGIV invasion caused an intestinal inflammatory response. Studies related to rotavirus, reovirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), astrovirus, and other viruses have extensively reported cases of intestinal inflammation caused by viral infection [42]. NF-κB is hypothesized to serve as a significant transcription factor implicated in inflammatory diseases of the intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…The subject requires further research. Czech studies show a poor response to mumps vaccination [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%